Homology Modeling of MDR1 Gene MDR1_ENTHI of E. histolytica & its Molecular Docking with Anti-Entamoeba Histolytica Agents - K. Singla, Rajeev (Current Topics in Medicinal Chemistry, 2015)
To investigate the theoretical model of the three-dimensional structure of multidrug resistance protein 1(P-glycoprotein, expressed by MDR1 gene of E. histolytica) and its molecular docking with anti-amoebic agents. The theoretical model of multidrug resistance protein 1(P-glyoprotein, expressed by MDR1 gene of E. histolytica) was predicted by homology modeling on the structure of the 3G61. Docking studies were performed to investigate the interaction of p-glycoprotein with antiamoebic gents. MRPEH1F is significant model for p-glycoprotein and have total of 114 amino acid residues. The model is well supported by cross validation data generated after analyzing criss-cross residues, local geometry check as well as ramachandran plot. Molecular docking of MRPEH1F revealed that all the test molecules have strong binding affinity along with significant interactions. Henceforth, none of the molecules will probably be effective for the multidrug resistant strains of E. histolytica.
Keywords: Entamoeba histolytica